Kształcenie w zakresie grafiki w szkolnictwie artystycznym Krakowa, Lwowa i Wilna w latach międzywojennych - Boguszewska, Anna (Biuletyn Historii Wychowania, 2013)
Training in graphics in the artistic education of Cracow, Lvov and Vilnius during the interwar years (1918–39) The beginnings of art education in Poland are connected with the cities of Cracow, Vilnius and Warsaw in the 18th and 19th centuries. In the interwar period (1918–39), in addition to the most powerful graphics education center in Warsaw, this discipline of art developed intensively in the art schools in Lvov, Cracow and Vilnius. The development of graphics in the Cracow Academy is related to the artistic and educational activities of Józef Pankiewicz. In 1923, the independent Department of Graphic Arts was established, conducted by John Wojnarski in collaboration with Andrzej Jurkiewicz and Jan Rubczak. The next outstanding teachers are Ludwik Gardowski and Konrad Strzednicki. Graphics education in the Municipal School of Art Industry (Miejska Szkoła Przemysłu Artystycznego) in Cracow is headed by Witold Chomicz. Graphics education in Lvov is linked to the activity of such artists as Ludwik Tyrowicz and Maria Rużycka. Ferdynand Ruszczyc, Bonawentura Lenart introduce the study of graphics into the curriculum of the Faculty of Fine Arts at Stefan Batory University in Vilnius. Since 1930, Jerzy Hoppen started the graphics workshop. In the 1930s, the graphic arts established a permanent and significant position in Polish art education.